Physical and Chemical Quality of Rice Straw Silage Made by The Addition of Bali Cattle Rumen Fluid - I M., Suadnyana; Cakra, I G. L. O.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the physical and chemical quality of rice straw silage made by the addition of Balinese cattle rumen fluid. The study was conducted in Banjar Buda Manis, Sidemen Village, Sidemen District, Karangasem Regency. Silage analysis was carried out at the Animal Nutrition and Food Laboratory, Faculty of Animal Husbandry, Udayana University. The design in the study was complete random concoction with four treatments and four replications. Treatment A (rice straw silage without rumen fluid) "control", B (rice silage straw with additional sterile rumen fluid 50 ml / kg straw), C (silage rice straw with additional fresh rumen liquid 25 ml / kg and sterile rumen fluid 25 ml / kg of straw) and D (rice straw silage with added fresh rumen liquid 50 ml / kg straw). The variables observed were physical quality including pH, fungi, color, aroma, and silage texture, while chemical qualities were: dry matter (DM), organic matter (OM), crude fat (CF), crude fiber (CF’), crude protein (CP), and ash. The results showed, in addition to the PK and SK variables showed a non-significant effect (P> 0.05). The silage CP levels in D treatment were significantly higher than treatments A, B, and C respectively at 11.12, 8.88 and 1.27%, and CF’ levels of D treatment were significantly lower than treatments A, B, and C is 22.06, 13.64 and 8.46%, respectively. The results of this study can be concluded that rice straw silage added with rumen fluid of 50 ml / kg can reduce SK content and increase PK content, while physical quality shows differences which is not real.   Keywords :  Rumen fluid, rice straw, silage physical quality, silage chemical qualiy